A Compact Batch Injection Analysis Cell for Screen Printed Electrodes: A Portable Electrochemical System for On‐site Analysis. Issue 8 (10th March 2016) - Richter, Eduardo M.; Tormin, Thiago F.; Cunha, Rafael R.; Silva, Weberson P.; Pérez‐Junquera, Alejandro; Fanjul‐Bolado, Pablo; Hernández‐Santos, David; Muñoz., Rodrigo A. A.
Abstract: Herein, a compact batch injection analysis cell for screen printed electrodes (BIASPE cell) is reported. The proposed system shows several requirements of a portable system that include easy‐to‐operate ("user‐friendly"), high‐speed quantitative and qualitative analysis, excellent cost effectiveness, and low‐power requirements (all auxiliary components are battery‐powered). Similar to analytical microsystems, small volumes of samples (5 to 100 μL) are required for analysis, however, the robustness of the system here proposed is considerably higher. The combination of the BIASPE cell with battery‐powered accessories (electronic micropipette, potentiostat and tablet or laptop computer) can be considered as a robust portable electroanalytical system. Electrochemical methods with portable characteristics can be now easily developed. Abstract :